NURSING SERVICE QUALITY STRATEGY IN INCREASING PATIENT LOYALTY AT BUNDA SEJATI HOSPITAL TANGERANG - Tri Hutami, Wulan; Kustiyani, Rahmi; Janah, Miftahul; Muljadi, Muljadi (Univesitas Muhammadiyah Tangerang, 2025)
Health institutions such as hospitals are a form of service in the field of services so they must provide the best form of service to patients to increase patient loyalty at Bunda Sejati Hospital Tangerang. Patient loyalty is one of the key indicators of a hospital's success. When patients feel satisfied and confident in the services provided, they are more likely to return for future treatment as well as recommend the hospital to their family and friends. The purpose of this study is to analyze the quality strategy of nursing services in increasing patient loyalty at Bunda Sejati Hospital Tangerang. In this study, direct observation techniques were used, then interviews and documentation. Based on the discussion in this study, the results obtained are that the service quality strategy consists of several indicators to increase patient loyalty at Bunda Sejati Tangerang Hospital.